The Association of Parental Feeding Style and Sociodemographic Characteristics with Child Anxiety in Preschool Children - Hatice Başkale; Emsal Akgül Koç; Perihan Solmaz (Sakarya Üniversitesi Holistik Sağlık Dergisi)
Objective: This descriptive, cross-sectional study aims to determine the relationship between parent feeding style and anxiety in children. Methods: The research was conducted with 338 mothers with children aged 3-6 years. Sociodemographic Information Form, Revised Preschool Anxiety Scale and the Parent Nutrition Style Questionnaire were used for data collection. Results: The mean Preschool Anxiety Scale scores significantly differed concerning the number of children’s siblings, mothers’ employment, fathers’ employment, mothers’ education, fathers’ education and family income. There was a significant positive weak correlation between anxiety levels and the mean scores on emotional feeding, instrumental feeding and the Parent Nutrition Style Questionnaire. Conclusion: Health professionals should be aware of several sociodemographic features that affect anxiety in children. Therefore, families at risk should be identified, their children should be closely monitored in terms of health problems like anxiety and depression, and appropriate interventions should be designed to prevent anxiety in children. Considering that parental feeding style affects eating habits in children, further studies are needed to examine the relationship between parental feeding behavior and anxiety in children.